Intellectual structure of market orientation: a citation/co-citation analysis. Issue 6 (2nd September 2019) - Hu, Chunjia; Song, Michael; Guo, Feng
Abstract : Purpose: The purpose of this paper is to employ a quantitative approach to explore the intellectual structure of the market orientation (MO) field over the course of its development. Design/methodology/approach: This research was conducted by using the bibliometric techniques of citation and co-citation analyses to investigate 1, 892 publications in the MO field from 1990 to 2016, as well as factor analysis and multidimensional scaling to present a clear visual experience of the knowledge structure of the MO filed. Findings: This study reveals meaningful outputs to assist in: delineating the critical authors, institutions and countries related to the study of MO; identifying the published documents that have had a significant influence on the field; clarifying the subfields that have developed from the MO field; and mapping the intellectual structure of the field in a two-dimensional space that allows for the visual representation of different themes. Research limitations/implications: Given the sheer volume of works that exist, these bibliometric techniques cannot completely measure, describe and present the entire intellectual structure of the MO field. Instead, co-citation analysis was performed using the data from only the top publications to identify the level of integration of the field, the changes of each knowledge group and the maturity of its evolution. Originality/value: First, this study extends the approach to identify the subject of MO from a quantitative perspective. Second, our analysis shows the intersection between the marketing discipline and management discipline in the MO literature. Finally, this study reveals the development tendency of the MO field in recent years. The results of this study are valuable to readers interested in MO research, especially those newly interested in this field.